(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The modern approach of antenatal care in pregnant women with rhesus-immunization means a timely diagnosis of the mutability of the rhesus (Rh) of the fetus through the blood of the mother, the detection of the anaemic syndrome and weight level of the fetus, the use of minimally invasive methods (diagnostic, therapeutic), as well as prevention of the development of immunization in pregnant women. The problem of rhesus-sensibilization in developed countries is rare, and only in immigrants. Objective: to examine and analyze the literature data of foreign and local authors on the relevance, prevalence, use of non-invasive methods of Rh-sensibilization prevention of hemolytic disease of the fetus. Search strategy: the search for information contained information such as regulatory documents, diagnostic protocols, and the conduct of RH-controversial pregnancy. Also in the databases Google Scholar, the Cochrane Library, PubMed, Library ru full-text scientific articles were used. Inclusion criteria: randomized, cohort study data, systematic reviews, diagnostic protocols, and Rh-conflict pregnancy. Exception criteria: practice, report, newspaper publications, articles describing theses. Results: studies have shown that the prophylactic purpose and administration of anti-D-immunoglobulin, which is used during 28-30 weeks of pregnancy, significantly reduces the development of immunization after childbirth. Conclusion: due to the wide application of anti-D-immunoglobulin in pregnant women and family planning, it will be possible to reduce the frequency of immunization, but the goal will be achieved only if a clear Complex prevention of Rh-immunization is developed, in which the appearance of hemolytic disease of the fetus occurs. Nevertheless, the diagnosis and treatment of hemolytic disease remains an urgent problem and requires the use of new possibilities of modern medicine in the field of genetics, ultrasound diagnostics, invasive and non-invasive methods.